Prevalence of Psychiatric Morbidities in Acute Coronary Heart Disease - Shoja shafti, Saeed (Hindawi Publishing Corporation, 2014)
Introduction. Psychiatric problems and stresses may deteriorate the prognosis of patients with IHD. So evaluating their frequency possibly will promote our perspective regarding their vital importance in the field of consultation-liaison psychiatry. Method and Materials. One hundred and one (101) patients with IHD were interviewed in CCU of a general hospital by a psychiatrist to find whether there was any relationship between cardiac events and psychiatric problems or stresses. Results. Cardiac events were significantly more prevalent among patients with both psychiatric problems and biological risk factors (P < 0.05). Also, the number of patients suffering from psychiatric problems was significantly more than cases without that (P < 0.05). There was a significant difference between male and female patients regarding the type of stress (P < 0.01). 79% of total stresses were experienced by patients who had as well psychiatric problems (P < 0.0001). In addition, there was significantly more dysthymic disorder in the acute group of patients in comparison with major or minor depressive disorder in the chronic group (P < 0.001). Conclusion. The high prevalence of psychiatric problems and psychosocial stresses among patients with IHD deserves sufficient attention by clinicians for detection, monitoring, and management of them.